The effect of leverage, liquidity, and accounting conservatism on tax avoidance with financial distress as a moderating variable - Salim, Vic Vincent; Setyarini, Yulia (Priviet Social Sciences Journal, 2025)
This study investigates how leverage, liquidity, and accounting conservatism impact tax avoidance. This study also investigates whether financial hardship can mitigate the association between tax avoidance and accounting conservatism. Using a purposive sampling technique, 63 food and beverage businesses listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023 constitute the sample for this study, yielding 189 observations in total. Multiple linear regression was used to analyze the data using SPSS PROCESS macro.. The findings indicate that (1) leverage significantly affects tax evasion. (2) Tax evasion is not significantly affected by liquidity. (3) The Effective Tax Rate (ETR) is significantly positively impacted by accounting conservatism, suggesting that conservatism actually lowers tax evasion. (4) It has been demonstrated that the association between tax evasion and accounting conservatism cannot be mitigated by financial hardship. that improves tax compliance, irrespective of the state of the business's finances.The findings suggest that corporate management should more carefully consider the actions taken and their associated risks concerning tax obligations.